Stress measurement at the interface between a Si substrate and diamond-like carbon/Cr/W films by the electronic backscatter diffraction method. (20th January 2016) - Zhou, Liqi; Xu, Guofu; Li, Xu; Wang, Xinwei; Ren, Lingling; Wang, Aiying; Tao, Xingfu
Abstract: Stress distribution characteristics at the interface between diamond-like carbon (DLC)/Cr/W films and a Si substrate were studied by an electronic backscatter diffraction (EBSD) system and transmission electron microscopy. Positive and negative stresses were distributed within the largest width of the Si/DLC interface, whereas the stress bands of homogeneous stress layers were observed at the interface between the Si substrate and the Cr layer. The stress bands of the Si/W interface were found to have the smallest width. The distinct characteristics of stress distribution at these interfaces are produced by the difference in the mass, energy, and diameter of the deposition ions/atoms as well as the different mechanisms of film growth.